2018
DOI: 10.1353/pla.2018.0005
|View full text |Cite
|
Sign up to set email alerts
|

LGBTQ Studies and Interdisciplinarity: A Citation Analysis of Master's Theses

Abstract: Emergent programs or newly established areas of study are often viewed as interdisciplinary.But how is interdisciplinarity defined or measured? The identification of research methods and the selection of objects of inquiry are significant elements in this definition. Citation analysis, however, also plays a role. Citation patterns in master's theses written at Concordia University in the field of LGBTQ studies at Concordia University in Montreal, Canada, indicate, at first glance, that the field is highly inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Whilst activist literature was sometimes cited, most citations targeted academic publications, were very interdisciplinary, and particularly drew upon medical papers. Within the field of LGBTQ+ studies, researchers drew upon a wide variety of disciplines but about half of it was about LGBTQ+ issues, at least as evidenced in the references in MSc dissertations at one Canadian university (Graziano, 2018). From a different perspective, a citation analysis of political science research showed that queer theory is marginal overall, with Judith Butler's work being the most influential (Smith & Lee, 2015).…”
Section: Characterisations Of Lgbtq+ Researchmentioning
confidence: 99%
“…Whilst activist literature was sometimes cited, most citations targeted academic publications, were very interdisciplinary, and particularly drew upon medical papers. Within the field of LGBTQ+ studies, researchers drew upon a wide variety of disciplines but about half of it was about LGBTQ+ issues, at least as evidenced in the references in MSc dissertations at one Canadian university (Graziano, 2018). From a different perspective, a citation analysis of political science research showed that queer theory is marginal overall, with Judith Butler's work being the most influential (Smith & Lee, 2015).…”
Section: Characterisations Of Lgbtq+ Researchmentioning
confidence: 99%